Using CVC (Consonant Vowel Consonant) With Picture Media In Teaching Vocabulary For The Young Learner - Ningsih, Wirda; Akhyar, Yundri; Puspita, Yenda (LPPI Yayasan Almahmudi bin Dahlan, 2023)
The study's goal is to determine whether using words with pictures and consonants increases students' language success in the second grade at SDIT Future Islamic School Pekanbaru. The pre-experimental technique was used in the study. The population of this research was the second grade students of SDIT Future Islamic School Pekanbaru in 2022/2023 academic year, There were two classes, II A and II B, each with 25 and 26 students, respectively. The total population was 51 students. The researcher used purposive sampling technique. The total sample of this research was 25 students. The result of the data analysis showed that the students’ vocabulary achievement, in the pre-test was X1 = 45.6and the post-test was X2 = 85.06. The result of the t-test value was (14.00) greater than the t-table value was (2.075). This indicates that the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. In other word, after the treatment, it can be concluded that the mean score of the students’ pre-test is smaller than the mean score of the students’ post-test (56.67 < 85.77). It means that the use of CVC word with pictre can increase the students’ vocabulary mastery in English.